2015
DOI: 10.3390/rs71215814
|View full text |Cite
|
Sign up to set email alerts
|

Precise Positioning of BDS, BDS/GPS: Implications for Tsunami Early Warning in South China Sea

Abstract: Global Positioning System (GPS) has been proved to be a powerful tool for measuring co-seismic ground displacements with an application to seismic source inversion. Whereas most of the tsunamis are triggered by large earthquakes, GPS can contribute to the tsunami early warning system (TEWS) by helping to obtain tsunami source parameters in near real-time. Toward the end of 2012, the second phase of the BeiDou Navigation Satellite System (BDS) constellation was accomplished, and BDS has been providing regional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…PPP has a few advantages over relative positioning techniques such as RTK: no restriction with inter-station distances, direct determination of position solution, simple data processing and global capability. As a result, PPP is widely applied to near real-time meteorology (Rocken et al 2005;Lu et al 2016), crustal deformation monitoring (Calais et al 2006), orbit determination of low (Zehentner and Mayer-Gürr 2015), earthquake and tsunami monitoring and early warning (Li et al 2013;Chen et al 2015), and other geoscience applications.…”
Section: Multi-gnss Precise Point Positioning (Ppp)mentioning
confidence: 99%
“…PPP has a few advantages over relative positioning techniques such as RTK: no restriction with inter-station distances, direct determination of position solution, simple data processing and global capability. As a result, PPP is widely applied to near real-time meteorology (Rocken et al 2005;Lu et al 2016), crustal deformation monitoring (Calais et al 2006), orbit determination of low (Zehentner and Mayer-Gürr 2015), earthquake and tsunami monitoring and early warning (Li et al 2013;Chen et al 2015), and other geoscience applications.…”
Section: Multi-gnss Precise Point Positioning (Ppp)mentioning
confidence: 99%
“…With the additional tracking of BDS constellations and therefore, a significant increase of observed satellites, GPS/BDS combined PPP could improve solution availability and accuracy by improving tracking geometry with a reduction of the position dilution of precision (PDOP) [ 9 ], especially in environments like urban canyons and ravines where there are limits in sky view. Chen et al [ 10 ] demonstrated that near real time GPS/BDS combined PPP solution show a higher degree of precision and better robustness, which is very important for tsunami early warning. Also, for GNSS-based precipitable water vapor retrieval, GPS/BDS combined PPP could obtain more accurate and reliable water vapor estimates than GPS-only or BDS-only PPP [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Instead of differencing carrier phase measurements between adjacent epochs in the VADASE method, TPP method adopts temporal-differenced measurements between a reference epoch and the current epoch, and there is almost no drift in the displacement derived from TPP method [ 37 ]. Chen et al retrieved the coseismic displacements of the Illapel Mw 8.3 earthquake and the Manila Trench Mw 8.0 earthquake with TPP method and found the accuracy of retrieved coseismic displacements with GPS/GLONASS and GPS/BDS observations was significantly better than that derived with GPS-only measurements [ 38 , 39 ]. Nevertheless, the precise orbit and clock products should be adopted in the TPP method.…”
Section: Introductionmentioning
confidence: 99%